The NO-donor FK409 improves mechanical properties of activated neonatal PMN - Ruef, Peter; Craciun, Eugenia Maria; Frommhold, David; Kuß, Navina; Fritzsching, Benedikt; Pöschl, Johannes; Koch, Lutz (Clinical hemorheology and microcirculation, 2012)
BACKGROUND Activated polymorphonuclear neutrophils (PMN) play an important role in the microcirculation. Nitric oxide (NO) reduces the sequestration of PMN in the narrow vessels of various organs and, therefore, may reduce organ injury during inflammation. OBJECTIVES Since PMN of term neonates show various functional differences compared to PMN in adults (decreased chemotaxis, decreased intracellular killing, decreased adhesion), we studied the influence of the semi-synthetical NO-donor FK-409 (4-Ethyl-2-hydroxyimino-5-nitro-3-hexenamide) on the deformability of IL-8 activated PMN in term neonates and adults. METHODS A cell transit analyzer (CTA) was used to study transit times of individual PMN through 8 μm filter pores, neutrophil elastase concentrations were determined by enzyme-immunoessay and activation of PMN was classified by mircroscopic evaluation. RESULTS The transit times of PMN activated by IL-8 in adults were 9.3 ± 2.9 s, in term neonates 10.7 ± 3.3 s. FK-409 improved the transit time of activated PMN in adults (5.4 ± 1.6 s) and in term neonates (5.6 ± 1.1 s). Despite of the functional differences of PMN in term neonates and adults, the improvement of the transit times by FK-409 was not different between the two groups. The NO donor decreased the neutrophil elastase concentrations and the morphological signs of activation in neonates and adults. CONCLUSIONS We conclude that the NO-donor FK-409 improves the microcirculation by increasing the deformability of IL-8 activated PMN. NO may reduce in neonates tissue damage by reduced PMN sequestration due to decreased PMN rigidity.